An Individual Finger Gesture Recognition System Based on Motion-Intent Analysis Using Mechanomyogram Signal - Ding, Huijun; He, Qing; Zhou, Yongjin; Dan, Guo; Cui, Song (Frontiers in Neurology, 2017)
Motion-intent based finger gesture recognition systems are crucial for many applications such as prosthesis control, sign language recognition, wearable rehabilitation system, and human computer interaction. In this paper, a motion-intent based finger gesture recognition system is designed to correctly identify the tapping of every finger for the first time. Two auto-event annotation algorithms are firstly applied and evaluated for detecting the finger tapping frame. Based on the truncated signals, the Wavelet packet transform (WPT) coefficients are calculated and compressed as the features, followed by a feature selection method which is able to improve the performance by optimizing the feature set. Finally, three popular classifiers including naive Bayes (NBC), K-nearest neighbor (KNN) and support vector machine (SVM) are applied and evaluated. The recognition accuracy can be achieved up to 94%. The design and the architecture of the system are presented with full system characterization results.